Mechanism of interaction of monovalent ions with phosphatidylcholine lipid membranes - Vácha, Robert; Jurkiewicz, Piotr; Petrov, Michal; Berkowitz, Max L; Böckmann, Rainer A; Barucha-Kraszewska, Justyna; Hof, Martin; Jungwirth, Pavel (The journal of physical chemistry. B, 2010)
Interactions of different anions with phospholipid membranes in aqueous salt solutions were investigated by molecular dynamics simulations and fluorescence solvent relaxation measurements. Both approaches indicate that the anion-membrane interaction increases with the size and softness of the anion. Calculations show that iodide exhibits a genuine affinity for the membrane, which is due to its pairing with the choline group and its propensity for the nonpolar region of the acyl chains, the latter being enhanced in polarizable calculations showing that the iodide number density profile is expanded toward the glycerol level. Solvent relaxation measurements using Laurdan confirm the influence of large soft ions on the membrane organization at the glycerol level. In contrast, chloride exhibits a peak at the membrane surface only in the presence of a surface-attracted cation, such as sodium but not potassium, suggesting that this behavior is merely a counterion effect.
Keywords: membránové lipidy; simulace molekulární dynamiky; Phosphatidylcholines; ionty; Membrane Lipids; Molecular Dynamics Simulation; Ions; fosfatidylcholiny